Study on dynamic sorption characteristics of modified biochars for ammonium in biogas slurry - Ding, Jingtao; Shen, Yujun; Ma, Yanru; Meng, Haibo; Cheng, Hongsheng; Zhang, Xi; Wang, Jian; Zhang, Pengyue (International Journal of Agricultural and Biological Engineering, 2020)
The objective of this study was to investigate the relationship between ammonium (NH4+-N) dynamic sorption capacity and physicochemical properties of modified biochars. Biochars, producing from three species of agricultural wastes of cornstalk (A), corncob (B) and sawdust (C) at 550°C, 600°C and 650°C, were modified by four methods of NaOH plus microwave (NaM), KOH (K), FeCl3 (Fe) and HNO3 (H). The static and dynamic adsorption experiments were conducted to investigate sorption characteristics of modified biochars on NH4+-N in slurry of piggery manure anaerobic digestate. Four modified biochars with better NH4+-N adsorption rates were selected through static kinetics adsorption tests, which showed that chemical reactions might have occurred during the NH4+-N sorption process and the maximum NH4+-N removal rates of B-550-Fe, A-550-NaM, A-550-K and C-600-NaM were 66.64%, 57.50%, 52.39% and 45.20%, respectively. The dynamic adsorption column experiment was conducted in a three-stage adsorption column packed with the selected three modified biochars. NH4+-N dynamic adsorption depended on the slurry inflow flow rate, the type of biochar and the depth of packed biochar. The optimal adsorption process was elected by the method of orthogonal experiment. The data showed that using deeper packed biochar and applying lower flow rates could be a better strategy to increase NH4+-N adsorption. The maximum NH4+-N removal rate in the slurry could reach 85.60% in the three-stage adsorption process. It concluded that NH4+-N adsorption in three-stage adsorption process could be an effective method to recover nitrogen from piggery manure anaerobic digestate.Keywords: modified biochar, biogas slurry, ammonium adsorption, sorption characteristicsDOI: 10.25165/j.ijabe.20201301.4697Citation: Ding J T, Shen Y J, Ma Y R, Meng H B, Cheng H S, Zhang X, et al. Study on dynamic sorption characteristics of modified biochars for ammonium in biogas slurry. Int J Agric & Biol Eng, 2020; 13(1): 234–240.